Survival and pathological response in pancreatic ductal adenocarcinoma after preoperative therapy with PD-1 blockade plus chemoradiotherapy followed by surgical resection - Elyar Abaydulla; Qi Li; Jialing Li; Defu Hu; Song Zhang; Shanshan Shen; Jian He; Aimei Li; Min Tang; Jun Chen; Huizi Sha; Liang Mao; et al. (Annals of Medicine)
Background Neoadjuvant PD-1 blockade plus chemoradiotherapy has resulted in improved clinical response in pancreatic ductal adenocarcinoma (PDAC); however, the effects on pathological response (PR) and survival remain unknown. This study was to identify the survival and PR of patients with PDAC undergoing surgery after neoadjuvant treatment (NAT) with PD-1 blockade plus chemoradiotherapy.Methods A retrospective cohort study was performed for PDAC patients undergoing resection after NAT, analyzing PR and survival prediction using clinicopathological and survival data.Results 47 patients were enrolled with 26 received neoadjuvant PD-1 blockade plus chemoradiotherapy (combined group) and 21 received PD-1 blockade plus chemotherapy (non-combined group). 6 patients (23.1%) and no patients achieved complete PR (CPR) in the combined and non-combined group. Age and tumor size decrease were independently associated with PR assessed by the CAP and MDACC system (p < 0.05). In the combined group, the 2-year overall survival (OS) rate, median OS and median disease-free survival (DFS) were 75.2%, 30.5 and 23.2 months, which were all better than those in the non-combined group (42.6%, 23.3 and 16.8 months), albeit with no significant differences. Portal vein (PV)/superior mesenteric vein (SMV) invasion (p = 0.034), resectability status (p = 0.019) and preoperative CA19-9 levels (p = 0.002) were significant prognostic factors for OS. Preoperative CA19-9 levels (p = 0.001) was an independent prognostic factor for DFS.Conclusions NAT with PD-1 blockade plus chemoradiotherapy was associated with a higher CPR rate in resected PDAC. Age and tumor size decrease were predictive factors for PR. PV/SMV invasion, resectability status, and preoperative CA 19-9 levels were independent prognostic factors for survival.